2012
DOI: 10.17221/317/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Application of FTIR spectroscopy for evaluation of hydrophobic/hydrophilic organic components in arable soil

Abstract: The main aim of this study was to determine the intensity of hydrophobic/hydrophilic components of the soil's organic matter as well as its hydrophobicity. Non-destructive Fourier Transform Infrared (FTIR) spectroscopy was used for the diagnosis and characterization of the basic classes of the chemical groups (hydrophilic and hydrophobic components) from which the organic matter in the soils is formed. Soil samples (depth 0-30 cm) were taken from the topsoil of the 70 sampling sites from the experimental field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…Matejkova and Simon (2012) and Winarna (2015) stated that hydrophobicity is the ratio between hydrophobic components and hydrophilic components in peat soil. Szajdak and Szatylowicz (2010) stated that the groundwater fluctuations affected the hydrophobicity of the peat as it could affect chemical composition of humic substances in peat soil.…”
Section: Hydrophobicity Of Peatmentioning
confidence: 99%
See 1 more Smart Citation
“…Matejkova and Simon (2012) and Winarna (2015) stated that hydrophobicity is the ratio between hydrophobic components and hydrophilic components in peat soil. Szajdak and Szatylowicz (2010) stated that the groundwater fluctuations affected the hydrophobicity of the peat as it could affect chemical composition of humic substances in peat soil.…”
Section: Hydrophobicity Of Peatmentioning
confidence: 99%
“…The functional groups C-H, C=C, OH and C=O attributed the nature of irreversible drying (hydrophobicity) on peat soil (Urbanek et al 2007;Utami et al 2009;Dlapa et al 2012;Matejkova and Simon 2012). Results of hydrophobicity interpretation showed that GWL-1 treatment with a final moisture content of 37% for BD-1 and 49.9% for BD-2 had entered the hydrophobicity.…”
Section: Hydrophobicity Of Peatmentioning
confidence: 99%
“…Artz, et al (2006) used the 1600/1030 bands ratio (carboxylate/polysaccharide) as an index of decomposition in peat, suggesting that the band near 1630 cm -1 represents a relatively recalcitrant form of organic C, probably a combination of lignin and humic substances. Other authors (Ellerbrock, et al, 2005(Ellerbrock, et al, , 2009Matějková and Šimon, 2012) proposed measuring the ratio of absorption bands related to relatively hydrophobic (3000-2800 cm -1 ) and hydrophilic (1740-1698 and 1640-1600 cm -1 ) SOM functional groups. The hydrophobic/hydrophilic functional groups ratio was used to predict the wettability or hydrophobicity of soils (Ellerbrock, et al, 2005).…”
Section: Soil Organic Matter Characterizationmentioning
confidence: 99%
“…It is of great importance to know the intensity of these bands, because with these can be estimated the hydrophilic organic components. It was found in [51] that these band lengths correlate significantly with OC groups and also with soil N.…”
Section: Spectral Characteristics Of Soilsmentioning
confidence: 99%